Parameters Affecting Image-guided, Hydrodynamic Gene Delivery to Swine Liver - Kenya Kamimura; Takeshi Suda; Guisheng Zhang; Yutaka Aoyagi; Dexi Liu (Elsevier, 2013)
Development of a safe and effective method for gene delivery to hepatocytes is a critical step toward gene therapy for liver diseases. Here, we assessed the parameters for gene delivery to the livers of large animals (pigs, 40-65 kg) using an image-guided hydrodynamics-based procedure that involves image-guided catheter insertion into the lobular hepatic vein and hydrodynamic injection of reporter plasmids using a computer-controlled injector. We demonstrated that injection parameters (relative position of the catheter in the hepatic vasculature, intravascular pressure upon injection, and injection volume) are directly related to the safety and efficiency of the procedure. By optimizing these parameters, we explored for the first time, the advantage of the procedure for sequential injections to multiple lobes in human-sized pigs. The optimized procedure resulted in sustained expression of the human α-1 antitrypsin gene in livers for more than 2 months after gene delivery. In addition, repeated hydrodynamic gene delivery was safely conducted and no adverse events were seen in the entire period of the study. Our results support the clinical applicability of the image-guided hydrodynamic gene delivery method for the treatment of liver diseases.